Abordagem metabolômica para a caracterização de diferentes tipos de doenças hepáticas colestáticas - Oliveira, Juliana Magalhães de (Universidade Federal de São Carlos, 2024)
Hepatic cholestasis is characterized by the reduction and/or obstruction of bile flow to the duodenum due to hepatocyte dysfunction during the synthesis or secretion of bile, leading to a cycle of pathological consequences. One type of cholestatic liver disease is Progressive Familial Intrahepatic Cholestasis type 3 (PFIC3), a recessive autosomal hereditary disease that affects the liver’s secretion, flow, or excretion of bile salts. This can lead to increased hepatotoxicity due to high concentrations of bile salts, causing liver damage. Late diagnosis of PFIC3 is common as it can only be unequivocally diagnosed through genetic tests. Therefore, alternative diagnostic methods that allow rapid diagnosis through blood or urine are attractive and necessary. Primary Sclerosing Cholangitis (PSC) and Primary Biliary Cholangitis (PBC) are autoimmune cholestatic liver diseases triggered by a genetic predisposition. In PBC, inflammation occurs in the intrahepatic bile ducts, while in PSC, inflammation occurs in the intra- and extrahepatic bile ducts, which can damage liver cells and cause progressive fibrosis deposition. PBC and PSC, if not treated, can lead to cirrhosis and liver failure. In Brazil, around 58.6% of patients with PSC have inflammatory bowel disease and are at risk of developing colorectal cancer. Chapter I aimed to understand better the pathological mechanisms underlying PBC through untargeted metabolomics analyses on plasma and urine samples from individuals diagnosed with PBC (n=30) and a control group of healthy individuals (HC; n=20). For this, liquid chromatography coupled to high-resolution mass spectrometry (LC-HRMS) was used, and the data were processed using multi- and univariate statistical methods. The results showed that 47 plasma metabolites and 46 urine metabolites showed statistically significant differences between PBC and the control group (HC) (p ≤ 0.05). The most important changes were observed in metabolites related to lipid metabolism, such as bile acids, phospholipids, fatty acids, and branched-chain amino acids. These findings indicated a metabolic profile that may aid in identifying new and potential biomarkers and monitoring PBC already being treated with ursodeoxycholic acid (UDCA). Chapter II aimed to perform metabolic discrimination between the different types of cholestasis (PBC, PSC, and PFIC3) in plasma and urine samples from patients undergoing treatment with UDCA. Using an untargeted metabolomics approach based on LC-HRMS analyses, 134 plasma metabolites, out of which 92 were statistically significant (p ≤ 0.05 and q ≤ 0.05). Among these, 43 lipid species (bile acids, glycerophospholipids, fatty acids, and carnitines) were detected, in addition to 30 amino acids, and 7 carbohydrates. Considering the urine samples, 76 metabolites were identified, of which 50 were considered statistically significant (p ≤ 0.05 and q ≤ 0.05). The main classes of metabolites discriminating between the different hepatic cholestasis included lipids, amino acids, carbohydrates, and organic acids. These results can help distinguish between cholestatic liver diseases, contributing to more accurate diagnoses and promoting personalized medicine. In this way, the identification of these metabolites not only improves the understanding of biochemical alterations correlated with cholestatic liver diseases but also promotes new opportunities in the search for more effective and individualized treatments.
Metabolomic approaches for the characterization of different types of cholestatic liver diseases
Keywords: Metabolômica; Metabolomics; Espectrometria de massas de alta resolução; High-resolution mass spectrometry; Cromatografia líquida; Liquid chromatography; LC-HRMS; Colestase intra-hepática familiar tipo 3 (PFIC-3); Progressive familial tntrahepatic cholestasis type 3 (PFIC-3); Colangite biliar primária (CBP); Primary biliary cholangitis (PBC); Colangite esclerosante primária (CEP); Primary sclerosing cholangitis (PSC); CIENCIAS EXATAS E DA TERRA::QUIMICA